Transcriptional coupling (Mfd) and DNA damage scanning (DisA) coordinate excision repair events for efficient Bacillus subtilis spore outgrowth - Valenzuela‐García, Luz I. (Microbiologyopen, 2018)
The absence of base excision repair (BER) proteins involved in processing ROS‐promoted genetic insults activates a DNA damage scanning (DisA)‐dependent checkpoint event in outgrowing Bacillus subtilis spores. Here, we report that genetic disabling of transcription‐coupled repair (TCR) or nucleotide excision repair (NER) pathways severely affected outgrowth of ΔdisA spores, and much more so than the effects of these mutations on log phase growth. This defect delayed the first division of spore′s nucleoid suggesting that unrepaired lesions affected transcription and/or replication during outgrowth. Accordingly, return to life of spores deficient in DisA/Mfd or DisA/UvrA was severely affected by a ROS‐inducer or a replication blocking agent, hydrogen peroxide and 4‐nitroquinoline‐oxide, respectively. Mutation frequencies to rifampin resistance (Rif(r)) revealed that DisA allowed faithful NER‐dependent DNA repair but activated error‐prone repair in TCR‐deficient outgrowing spores. Sequencing analysis of rpoB from spontaneous Rif(r) colonies revealed that mutations resulting from base deamination predominated in outgrowing wild‐type spores. Interestingly, a wide range of base substitutions promoted by oxidized DNA bases were detected in ΔdisA and Δmfd outgrown spores. Overall, our results suggest that Mfd and DisA coordinate excision repair events in spore outgrowth to eliminate DNA lesions that interfere with replication and transcription during this developmental period.